2009
DOI: 10.1152/ajpcell.00255.2009
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ regulates retinal pigment epithelial fluid transport

Abstract: The present experiments show that IFNgamma receptors are mainly localized to the basolateral membrane of human retinal pigment epithelium (RPE). Activation of these receptors in primary cultures of human fetal RPE inhibited cell proliferation and migration, decreased RPE mitochondrial membrane potential, altered transepithelial potential and resistance, and significantly increased transepithelial fluid absorption. These effects are mediated through JAK-STAT and p38 MAPK signaling pathways. Second messenger sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 72 publications
(87 reference statements)
2
32
0
Order By: Relevance
“…This is consistent with a recent study that reported that ␤-HB is a preferred substrate for glutamate synthesis in neurons (36), where glutamate acts as an important neurotransmitter and as a cofactor for glutathione and amino acid synthesis. In our experiments, we found that 13 C ␤-HB metabolism was unaffected by the presence or absence of unlabeled glucose (data not shown), suggesting that glucose metabolism pathways do not compete with ␤-HB metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a recent study that reported that ␤-HB is a preferred substrate for glutamate synthesis in neurons (36), where glutamate acts as an important neurotransmitter and as a cofactor for glutathione and amino acid synthesis. In our experiments, we found that 13 C ␤-HB metabolism was unaffected by the presence or absence of unlabeled glucose (data not shown), suggesting that glucose metabolism pathways do not compete with ␤-HB metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, host defense and efficient mucociliary clearance is achieved by the stimulation of chloride transport and subsequent regulation of airway surface hydration. Other mediators have been reported to play a role in epithelial transport, including pro-inflammatory mediators, such as prostaglandins, leukotrienes and interferon gamma [24][25][26] as well as pro-resolution mediators 27 . In other models, such as the colon adenocarcinoma-derived cell line T84, the same treatment reduced CFTR expression and function 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous experiments we have used these primary cultures to determine the expression, polarization and function of plasma membrane transport proteins and identify specific signaling pathways that regulate RPE function [1][2][3][4][5][6][7][8][9][10][11] These characteristics as they are accumulated provide a validation set of properties that can be applied to each cell generation. The experiments summarized below identify the proteins that determine transepithelial fluid transport and the integrity of the paracellular pathway.…”
Section: Functional Validation Of Hfrpe Cell Culturementioning
confidence: 99%